1996
DOI: 10.1002/eji.1830260611
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of interleukin‐1β gene expression in activated RAW 264.7 macrophages by interferon‐γ

Abstract: The ability of interleukin-1 (IL-1) to activate epidermal cell populations supports its role as a key cytokine in the pathogenesis of a number of inflammatory skin diseases. In the present study, we have examined the effect of interferon (IFN)-gamma on the expression of the IL-1 beta gene in mouse RAW 264.7 macrophages activated by lipopolysaccharide (LPS) plus tumor necrosis factor (TNF)-alpha. Incubation of macrophages with both LPS and TNF-alpha resulted in the expression of both IL-1 beta and inducible nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…1) observations in the murine macrophage cell line RAW 264.7. (9) The specific effect of IFN was supported by the observation that anti-IFN antibody abrogated the inhibitory effect of IFN on LPS-stimulated IL-1 expression (Fig. 2).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…1) observations in the murine macrophage cell line RAW 264.7. (9) The specific effect of IFN was supported by the observation that anti-IFN antibody abrogated the inhibitory effect of IFN on LPS-stimulated IL-1 expression (Fig. 2).…”
Section: Discussionmentioning
confidence: 65%
“…(5) An IFN regulatory cytokine, IL-18 (IL-18), a proximal stimulus of IFN expression, (6) also exists in a proform that requires proteolytic cleavage by caspase-1 to produce a functionally active cytokine. (7,8) Chujor et al (9) observed that IFN could selectively inhibit lyopolysaccharide (LPS)-induced IL-1 in the murine macrophage cell line RAW 264.7. The relevance of this observation to the in vivo control of the inflammatory response was not determined, however.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of RAW 264.7 cells stimulated with LPS, IFN-␥ was reported to induce hyporesponsiveness to LPS and reduce the production of TNF-␣ (50). Another report also showed that IFN-␥ strongly suppressed the expression of IL-1 ␤ gene stimulated with LPS (51). These data suggest that IFN-␥ acts as inhibitory cytokine under the chronically inflammatory conditions stimulated with LPS.…”
Section: Discussionmentioning
confidence: 72%
“…In fact, it has been suggested that the agents that increase cAMP levels could be inhibitors of macrophage activities (21,36). It has also been reported that LPS inhibits, in some cases, certain aspects of IFN-␥-induced macrophage activation, whereas, in other cases, it increases activation (16,(37)(38)(39). Both cAMP-increasing agents and LPS inhibit M-CSF-dependent proliferation of macrophages.…”
Section: Resultsmentioning
confidence: 99%